Dynamic routing and wavelength assignment: Artificial bee colony optimization - Rashedi, A.; Kavian, Y. S.; Ansari-Asl, K.; Ghassemlooy, Z. (2011 13th International Conference on Transparent Optical Networks, 2011)
In this paper an application of intelligent systems for optical networks design is proposed. The Routing and Wavelength Assignment (RWA) in Dense-Wavelength-Division-Multiplexing (DWDM) optical networks under dynamic traffic patterns is addressed. We mainly focus on how to apply Artificial Bee Colony (ABC) algorithm to solve dynamic RWA problem by minimizing the blocking probability for a sequence of arrival connection requests subject to total number of wavelengths in optical network and wavelength continuity constraints. Simulation results demonstrate that the proposed ABC based DRWA algorithm has better performance in reducing the blocking probability comparing to Fixed-alternate routing algorithm.